Improved safety checklist analysis approach using intelligent video surveillance in the construction industry: a case study. Issue 4 (2nd October 2021) - Guo, Shengyu; Li, Jichao; Liang, Kongzheng; Tang, Bing
Abstract : The construction industry is extremely high risk, and safety checklist analysis is a widely used approach for safety assessment. To overcome its limitations, this article proposes an improved safety checklist analysis approach using intelligent video surveillance to replace on-site inspection. Then, a case study on metro tunnel construction is adopted to illustrate the process. First, the checklist is prepared. Second, the inspection items are correlated with construction areas, and intelligent cameras are positioned to cover the major areas of the construction site to guarantee that all the items can be checked. Thus, problems with inspection items are automatically identified and recorded. Third, the inspection items are marked by a remote scoring mechanism for safety assessment. Finally, the efficiency of the improved approach is tested by a comparative analysis among three groups. The application results indicate the feasibility of the improved approach for evaluating the safety management performance at construction sites.